2008
DOI: 10.1007/s10549-008-0210-3
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for the treatment of hot flashes in breast cancer patients, a randomized, controlled trial

Abstract: Acupuncture has been used to treat the problem of hot flashes in healthy postmenopausal women. The object of this study was to investigate the efficacy of acupuncture in women with breast cancer suffering from hot flashes as a result of anti-oestrogen medication. In a prospective, controlled trial, 59 women suffering from hot flashes following breast cancer surgery and adjuvant oestrogen-antagonist treatment (Tamoxifen) were randomized to either 10 weeks of traditional Chinese acupuncture or sham acupuncture (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
121
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(123 citation statements)
references
References 24 publications
(38 reference statements)
2
121
0
Order By: Relevance
“…14 -23 Recent studies have reported that acupuncture is effective in reducing vasomotor symptoms in patients who have breast cancer and who are receiving tamoxifen, [16][17][18][19][20][21][22] but there is no consensus on the optimum treatment frequency or the duration of acupuncture in these patients. The duration of acupuncture treatment in this study was 4 weeks, which is a relatively short period compared to that in previous studies (range, 4-12 weeks).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 -23 Recent studies have reported that acupuncture is effective in reducing vasomotor symptoms in patients who have breast cancer and who are receiving tamoxifen, [16][17][18][19][20][21][22] but there is no consensus on the optimum treatment frequency or the duration of acupuncture in these patients. The duration of acupuncture treatment in this study was 4 weeks, which is a relatively short period compared to that in previous studies (range, 4-12 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Recent studies have suggested that acupuncture is effective in reducing vasomotor symptoms among menopausal women [11][12][13] as well as patients with breast cancer receiving tamoxifen (Table 1). [14][15][16][17][18][19][20][21][22][23] A randomized controlled trial 17 reported favorable effects of acupuncture compared with sham acupuncture for hot flashes in patients with breast cancer, although another randomized controlled trial 18 failed to show any such effects. Walker et al 19 compared acupuncture with venlafaxine and demonstrated that acupuncture was as effective as venlafaxine.…”
mentioning
confidence: 99%
“…In addition, acupuncture, mind-body techniques, and massage may help relieve side effects and improve patients' physical and emotional well-being. At present, about one in three breast cancer patients discontinues her hormone treatments against medical advice; in such cases CAM interventions can improve compliance by reducing hot flashes or joint pain [11][12][13].…”
Section: The Concept Of Integrative Oncology (Io)mentioning
confidence: 99%
“…There is evidence to support the use of acupuncture in patients in palliative care for a range of symptoms including pain, [8][9][10][11][12][13][14][15][16][17][18][19] nausea and vomiting, [20][21][22][23][24][25][26][27] dyspnoea, [28][29][30] xerostomia, [31][32][33][34][35][36][37] hot flushes, [38][39][40][41][42][43][44] fatigue 45 46 and detrusor instability. 47 48 There is also limited (anecdotal) evidence for use of acupuncture in a variety of other conditions such as anxiety, skin ulcer healing, intractable hiccough, dysphagia, radiation rectitis and uraemic pruritus.…”
Section: Introductionmentioning
confidence: 99%